1998
DOI: 10.1136/aim.16.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture Treatment on Heel Pain Due to Plantar Fasciitis

Abstract: Eighteen patients attending an orthopaedic outpatient clinic with a year or more's history of heel pain due to plantar fasciitis were studied. All had had conservative treatment of physiotherapy and shoe-support without significant pain relief before acupuncture was offered, and thus acted as their own controls for the purposes of the study. The following traditional points were needled: Taixi (KI.3), Kunlun (BL.60) and Sanyinjiao (SP.6). Pain was assessed by a 100mm visual analogue scale (VAS) before treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 14 publications
0
45
0
Order By: Relevance
“…Since there is scientifi c evidence supporting a link between electrical stimulation of acupuncture points and the release of endorphins, these researchers also theorised that electro-acupuncture could activate the body's pain relief system, increasing the concentration of endorphins in the central nervous system and decreasing the amount of pain signals that arrive at the spinal cord level. (30,31) The present study was not without limitations. As a single author performed this review, the possibility of bias in study selection and appraisal, which could have impacted its results, cannot be disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is scientifi c evidence supporting a link between electrical stimulation of acupuncture points and the release of endorphins, these researchers also theorised that electro-acupuncture could activate the body's pain relief system, increasing the concentration of endorphins in the central nervous system and decreasing the amount of pain signals that arrive at the spinal cord level. (30,31) The present study was not without limitations. As a single author performed this review, the possibility of bias in study selection and appraisal, which could have impacted its results, cannot be disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…muscle tissue) and non-TrP structures (i.e. neural and connective tissues) in combination, or non-TrP structures alone, is effective for the reduction of pain and disability in knee osteoarthritis,505051,8183,8590,166168 hip osteoarthritis,53,9194 piriformis syndrome,60 carpal tunnel syndrome,36,37,40,41,44,45,47 migraine,95101 tension type headache,97,98,102 temporomandibular disorder,59,67,103107 shoulder pain,108110 neck pain,23,24,29,35,61,6365,80,111114 low back pain,4,5,19,20,66,69,115125 and plantar fasciitis 48,49,54,56,126,127…”
Section: Trp Needling Is Only One Kind Of Dry Needlingmentioning
confidence: 99%
“…While many of these studies directly use the term ‘dry needling’,5,18,21,26,33,56,64,67,104,110 in their methodology, other studies use alternative terminology such as ‘deep dry needling’,67 ‘superficial dry needling’,55,128 ‘TrP acupuncture’,20,80 ‘paraspinal needling’,64 ‘intramuscular and nerve root needling’,65 ‘needle electrical intramuscular stimulation’,129 ‘needle release’,113 ‘acupuncture needling’,63,113 ‘needling therapy’,17 ‘acupuncture’36–38,40,41,47,49–55,61,69,72,8188,90,92,94100,105108,112,115117,119123,130135 and ‘electroacupuncture’ 37,46,93,126,127,136139. Some studies have even chosen to use both ‘acupuncture and dry needling’19,23,24,62,77 in their titles.…”
Section: Trp Needling Is Only One Kind Of Dry Needlingmentioning
confidence: 99%
See 1 more Smart Citation
“…While this has the merit of simplicity, it may not reflect a reality that is complex. This review has shown that MTPs may give additional benefit when added to classical acupuncture 37 and also that acupuncture unrelated to MTPs confers significant benefits. 34 Clinical experience (RJC) shows that some patients have MTPs related to their heel pain and others do not; there is a need to explore the possibility that these are two pathologically distinct groups, requiring different treatment approaches.…”
Section: Tenderness Scores Changed Littlementioning
confidence: 99%